Doege-Potter syndrome and pericardic effusion as lung carcinoma early manifestations - Carrillo, Leonidas (2008)
A 52 year-old man was admitted to our hospital because of large pericardial effusion and symptoms of recurrent hypoglycaemia. He had no history of smoking or diabetes mellitus and was taking no medication. Diagnostic pericardiocentesis was performed and 1 430 mL of bloody-stained fluid was obtained. The exudate showed neutrophils positive to adenosin deaminase (ADA) test. Chest X-ray and computed tomography showed a left lung hilar mass resembling a lung neoplasm, with pleural and pericardial effusion. It was a lung cancer of unusual presentation, with pleural and pericardial metastasis and a paraneoplastic syndrome characterized by recurrent hypoglycaemia as initial manifestation.